2007
DOI: 10.1523/jneurosci.2152-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Reduction of γ-Secretase Attenuates Amyloid Burden and Limits Mechanism-Based Liabilities

Abstract: Although ␥-secretase is recognized as a therapeutic target for Alzheimer's disease, side effects associated with strong inhibition of this aspartyl protease raised serious concerns regarding this therapeutic strategy. However, it is not known whether moderate inhibition of this enzyme will allow dissociation of beneficial effects in the CNS from mechanism-based toxicities in the periphery. We tested this possibility by using a series of mice with genetic reduction of ␥-secretase (levels ranging from 25 to 64% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 39 publications
4
63
1
1
Order By: Relevance
“…Myeloid progenitors are also sensitive to Presenilin dose (Qyang et al 2004), where a multipotent granulocyte/ monocyte progenitor expands in the spleen. Similar dose sensitivity was observed in nicastrin heterozygotes (Li et al 2007). It is possible that in all these cases, a titration mechanism similar to the one described here is in play.…”
Section: Rbp-jksupporting
confidence: 83%
“…Myeloid progenitors are also sensitive to Presenilin dose (Qyang et al 2004), where a multipotent granulocyte/ monocyte progenitor expands in the spleen. Similar dose sensitivity was observed in nicastrin heterozygotes (Li et al 2007). It is possible that in all these cases, a titration mechanism similar to the one described here is in play.…”
Section: Rbp-jksupporting
confidence: 83%
“…Constitutive as well as conditional knock-out mouse studies have demonstrated that mice with selective ablation of different subunits exhibit different severity of Notch-deficient phenotypes, depending upon the age and subunit targeted (10,41,(55)(56)(57)(58)(59)(60)(61)(62). Hence, these studies suggest that isoform-selective inhibitors offer another avenue for circumventing Notch-related toxicity observed with first generation ␥-secretase inhibitors (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential confounders include personality, psychosocial variables, and physical activity. 20,21 Physical activity is protective against cognitive decline and dementia. 18 Outdoor physical activity may lead to increased exposure to ultraviolet radiation, which increases skin cancer risk.…”
mentioning
confidence: 99%
“…The relationship between cancer and AD may reflect differences in DNA methylation, 23 activity of the tumor suppressor gene p53, the enzyme Pin1, or the Wnt signaling pathway. 20 Additionally, NMSC-specific associations with AD can be attributed to mechanisms involving g-secretase signaling 21,24,25 through a Notch 1 signaling pathway. 26,27 This study has a number of limitations.…”
mentioning
confidence: 99%